(untitled) (Eurasian Research Bulletin, 2023)
The article describes the results of the evaluation of sperm donor bulls brought from abroad to the state enterprise "OZNASLCHILIK" according to their origin. The purpose of the study is to evaluate the degree of herd "Improving" effect of imported breeding bulls in order to use them in artificial insemination on a large scale